Transport outlook 2010: The potential for innovation - OECD; International Transport Forum (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2010)
This paper provides evidence on and discussion of recent developments in global transport markets and analyzes what policies look most promising for stabilizing CO2-emissions from light-duty vehicles. In the aftermath of the economic crisis, recovery is uncertain and unevenly spread across the globe. This has potential impacts on global trade patterns and commodity flows, and hence on key freight transport flows. For the management of future greenhouse gas emissions from transport, our analysis strongly suggests that technologies to improve fuel economy and ultimately transform the energy basis of transport are the key, as there are very strong upward pressures on demand volumes. This of course does not mean that demand management in transport is unjustified or does not contribute at all to greenhouse gas abatement, but its potential is limited so that technological improvement is at the core of climate change policy in the transport sector.
Keywords: 330